Evaluación de biofertilizante líquido de rizobacterias con crioprotectores celulares para la formulación de un inoculante biológico con aplicación en restauración ecológica (2021)
In this research, new formulations of a biological inoculant were developed from PGPR (Plant Growth Promoting Rhizobacteria) with Lactobacillus casei, Pseudomona Fluorescens and Azotobacter sp bacteria with biomaterials, performing in vitro tests to improve the useful life of the formulation for a later use in the field at a nursery scale, improving the adaptation conditions of plant species used in ecological restoration. In this investigation, bacterial strains that have been previously isolated, identified and preserved were activated, bacterial viability and purity were determined with macroscopic and microscopic identification. Finally, the production of inocula was carried out by liquid fermentation at a 200 ml scale with follow-up of growth curves and stability tests. Viable and pure microbial strains were obtained in three different formulations with sodium alginate, glycerol and carboxymethylcellulose for five months at room temperature, having three TRL6 liquid prototypes without gas production, with bacterial counts of up to 1x107 CFU / ml. It was possible to contribute to scientific knowledge, proposing a new biological formula that allows improving the nutrition of degraded soils, and proposing alternatives for the ecological restoration of high Andean forest ecosystems.